2018
DOI: 10.1111/joor.12700
|View full text |Cite
|
Sign up to set email alerts
|

A 2‐year longitudinal study of the relationship between masticatory function and progression to frailty or pre‐frailty among community‐dwelling Japanese aged 65 and older

Abstract: Our results confirm that masticatory function was associated with the progression to pre-frailty or frailty among community-dwelling individuals 65 years and older over the 2-year period of this longitudinal study. Of the masticatory function items evaluated, mixing ability and subjective chewing ability were associated with frailty progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(87 citation statements)
references
References 28 publications
5
77
1
4
Order By: Relevance
“…Among the longitudinal studies, Horibe et al reported that walking speed was significantly associated with decreasing occlusal force, but that hand grip strength and skeletal muscle index (SMI) were not significantly associated with decreasing occlusal force [24]. Tanaka et al found no significant association between occlusal force and the onset of sarcopenia [33].…”
Section: Occlusal Forcementioning
confidence: 99%
See 2 more Smart Citations
“…Among the longitudinal studies, Horibe et al reported that walking speed was significantly associated with decreasing occlusal force, but that hand grip strength and skeletal muscle index (SMI) were not significantly associated with decreasing occlusal force [24]. Tanaka et al found no significant association between occlusal force and the onset of sarcopenia [33].…”
Section: Occlusal Forcementioning
confidence: 99%
“…Mastication was evaluated by subjective or objective methods. Subjective masticatory ability was evaluated by questions about chewable food [12,13,16,19,20,24] or by asking participants to state how many of the 15 listed foods were chewable [11,15]. Objective masticatory performance was evaluated by assessing participants' ability to chew a piece of colored chewing gum [19,24,30] or a gummy jelly [23,33].…”
Section: Masticationmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, various cross-sectional and longitudinal studies have shown that frailty in community-dwelling older people is associated with decreases in oral functions such as occlusal force, tongue pressure and masticatory function. [9][10][11][12] Various items contribute to oral function; however, no standardized evaluation criteria for multiple oral functions have been determined. There is also little information on the effects of a combination of decreased oral functions on frailty.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of dentistry, there have been many studies regarding oral health status in frail older adults and a possible association between poor oral health conditions and frailty . However, there have been very few studies regarding frailty in the oral and maxillofacial regions, and there are no universally accepted indices or tools for evaluating the presence and severity of oral and maxillofacial frailty.…”
Section: Introductionmentioning
confidence: 99%